Peran Strategi BLUD dalam Mendukung Koperasi dan Usaha Mikro untuk Pertumbuhan Ekonomi Daerah - Seftian; Riske Yuan Vina Titasari; Angguliyah Rizqi Amaliyah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2025)
Cooperatives and micro-enterprises play a vital role in supporting national and regional economic structures, providing employment, distributing income, and encouraging economic activity among small and medium-sized enterprises (SMEs). In Malang Regency, this role is strengthened through the existence of the Regional Public Service Agency (BLUD) Revolving Fund, which is under the auspices of the Cooperatives and Micro-Enterprises Office. The BLUD Revolving Fund is tasked with providing more affordable financing access for cooperatives and micro-enterprises with low interest rates, simple procedures, and no administrative fees. This study aims to examine the strategic role of BLUD in supporting regional economic growth through productive financing and empowering cooperatives and micro-enterprises. This study uses a qualitative descriptive approach with data triangulation analysis methods, namely through document analysis, semi-structured interviews, and field observations. The results show that BLUD not only provides access to capital but also builds a sustainable small business development ecosystem. The revolving fund scheme offered encourages the transformation of cooperatives and MSMEs to become more professional, resilient, and independent in facing local and global economic challenges.